Development of Rice Field Tourism as an Attraction and Economic Opportunity for the Community in Pematang Johar Village - Kustiawan, Winda; Nasution, Nadila Syifa; Ritonga, Nur Anisyah; Hutasuhut, Intan Juliani (Holistic Science, 2025)
This study aims to develop rice field tourism as an icon of identity and attraction of Pematang Johar village through an action research approach. Pematang Johar Rice Field Tourism Village is a new tourist destination located in Dusun VI Rawa Badak, Labuhan Deli District, Deli Serdang Regency, on the outskirts of Medan City. This place offers beautiful natural scenery with a stretch of rice fields covering an area of 1,750 hectares which is the main attraction for tourists. The uniqueness of this destination lies in the natural rural atmosphere and various facilities such as bamboo bridges and gazebos that make it easy for visitors to enjoy the beauty of the rice fields without having to step on mud. The presence of this Rice Field Tourism Village not only attracts tourists, but also contributes to improving the local economy through income from the tourism sector.